2015
DOI: 10.1155/2015/172864
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Sensing Properties of Cu Doped ZnO Nanocrystalline Thin Films

Abstract: Undoped and Cu doped ZnO films of two different molarities deposited by spray pyrolysis using zinc nitrate and cupric chloride as precursors show polycrystalline nature and hexagonal wurtzite structure of ZnO. The crystallite size varies between 10 and 21 nm. Doping increases the transmittance of the films whereas the optical band gap of ZnO is reduced from 3.28 to 3.18 eV. With increment in doping the surface morphology changes from irregular shaped grains to netted structure with holes and then to net making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…From images shown in Figure 4, it was found that the undoped Cr 2 O 3 film had a surface more or less smooth. For the others, it is clear that the surface morphology of the films strongly depends on the Cu content [37], as long as these films seem to have more porosity compared to the undoped film.…”
Section: Results and Discussion A) Structural Characterizationmentioning
confidence: 99%
“…From images shown in Figure 4, it was found that the undoped Cr 2 O 3 film had a surface more or less smooth. For the others, it is clear that the surface morphology of the films strongly depends on the Cu content [37], as long as these films seem to have more porosity compared to the undoped film.…”
Section: Results and Discussion A) Structural Characterizationmentioning
confidence: 99%
“…The studies of semiconductor nanoparticles trigger have a big attention in the last years, that is due to their optical uniqueness and electrical properties (1).Recently, the synthesis characterization and processing of nanostructure materials are emerging and rapidly growing research work (1,2). Zinc oxide is a versatile material and well known to have a direct band gap of 3.37 eV at room temperature and has distinguishable performance in electronics, optics and photonics (3,4,5,6). Among the semiconductor nanoparticles, zinc oxide is an important II-VI semiconductor, which has been researched extensively,according to its broad spectrum of potential applications such as in catalysts (7).…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been published on the use of Cu for sensing different gases [ 14 , 15 , 16 , 17 ]. It is assumed that Cu 1+ ions substitute for the Zn 2+ in the ZnO lattice, reducing the electron concentration, and hence, a higher electrical resistivity is observed [ 18 , 19 , 20 , 21 , 22 ]. Cu-doped ZnO thin films have been prepared by several deposition techniques, such as pulsed-laser deposition, magnetron sputtering, spray pyrolysis and the sol-gel process [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%